Tsum Adjectives in Areal-Typological Perspective - Dhakal, Dubi Nanda (Nepalese Linguistics, 2025)
This paper presents the semantic and morphological features of Tsum adjectives. Additionally, comaprison of the inflectional suffixes in Tsum will be made with genetically neighbouring languages. The affixes -po, -mo appearing in the structure of affixes can be related to broader Tibetan languages. By contrast, some affixes that appear in deriving comparative and superlative forms can only be associated among sister languages.